BOARD GENDER DIVERSITY AS A MODERATOR IN THE CORPORATE GOVERNANCE AND FIRM VALUE RELATIONSHIP - Mochammad Arief Nur Firmansyah; Indrianawati Usman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the effect of corporate governance on firm value, with a particular emphasis on the moderating role of board gender diversity (BGD). A quantitative approach is employed using secondary data obtained from Bloomberg, covering publicly listed firms in Indonesia from 2017 to 2023. The analysis utilizes moderated regression analysis (MRA) with three alternative measures of BGD: dummy, proportion, and Blau Index. The results reveal that corporate governance, when assessed independently, does not have a significant direct effect on firm value. However, the interaction between corporate governance and BGD is found to be positive and statistically significant across all models, indicating that gender diversity enhances the governance–firm value relationship. These findings highlight the importance of inclusive board composition in strengthening governance effectiveness, particularly in emerging market contexts.